Pinjaman Online : Sebuah Respon Hukum Islam dan Hukum Positif - Adi, Asriadi Arifin; Irwandi, Irwandi (CV. Kalimasada Group, 2024)
This digital lifestyle trend has apparently spread to economic problems. The economic needs of society from conventional ones have shifted to utilizing financial technology, especially for generation Z people. Currently, the need to borrow funds is mostly done through fintech platforms which have spread widely in society. Finally, various companies that provide online loan financial services have also spread recently. The aim of this research is to examine the perspective of Islamic law and positive law on illegal online loans as well as legal protection for illegal online loan (Pinjol) users. The method used is a literature method with a normative approach which refers to statutory regulations which examine the rules and regulations related to the legal issue being handled. The results show that illegal online loans from the perspective of Islamic law are invalid. Meanwhile, in positive legal terms in civil law, illegal online lending is a transaction that does not meet the legal requirements of an agreement. In criminal law policy, to date there are no provisions in criminal law involving illegal lending services. As a form of protection for consumers, education and outreach to the public is needed, with the aim of more people understanding about current financial services.